Cinética da eliminação de cistos e resposta imune humoral sistêmica e secretora intestinal em gerbils (Meriones unguiculatus) infectados experimentalmente com Giardia duodenalis - Amorim, Rúbia Mara Rodrigues (2008)
Giardia duodenalis is one of the main causative agents of diarrhea worldwide, being transmitted by oral-fecal route. Giardiasis is usually self-limiting in immunocompetent individuals, indicating the presence of effective host defense mechanisms. The objective of that study was to determine the prepatent period and to evaluate the kinetics of elimination of cysts and the immune response humoral systemic (IgA, IgG1, IgG2a, IgM, IgE) and intestinal secretory (IgA) in gerbils (Meriones unguiculatus) inoculated, experimentally, with different doses of trophozoites of Giardia duodenalis, in the primary infection, reinfection, immunosuppression and reinfection/immunosuppression. We used 48 animals, 6-8 weeks old, distributed in 5 groups inoculated with different doses of trophozoites of G. duodenalis (101, 102, 103, 104 and 105) and a group control. Coproparasitology exams were carried out, daily, using the method of fluctuation in zinc sulfate 33%, to determine the prepatent period and the kinetics of elimination of cysts. Weekly, blood collections for retro-orbital puncture were performed and samples of feces were processed for obtaining of faecal extracts. In the 45th day after inoculation, the animals of each group were redistributed in 4 subgroups and submitted to the reinfection, immunosuppression or reinfection/immunosuppression. It was verified that all the gerbils inoculated with different trophozoites doses were susceptible to the primary infection, with prepatent period between 9 and 13 days. The reinfected animals didn't eliminate cysts and the immunosuppressed or reinfected/immunosuppressed again they presented recrudescence of the infection. The production of antibodies was induced by the parasite, although the systemics antibodies just reflect the stimulation of the immune response for G. duodenalis, since they don't act in the elimination of the parasite. In the reinfection it was observed fast production of both serum and secretory antibodies and the immunossuppressed animals they presented smaller levels of responsible antibodies for the control of the infection. Fecal IgA showed increase in the titles in the period in that absence of cysts was verified in the feces, could be correlated with the control of the giardiasis in this experimental model.